The Legality of Retail Fuel Sales - Falah Ilmania, Nurika; Nofi Sri Utami; Moh. Muhibbin (Jurusan Hukum Tatanegara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin, 2022)
Fuel Oil (BBM) is one of the basic needs of the community, as the management and distribution of BBM is protected by the State to be able to maintain the quality of BBM. However, the research found that there are rampant individual retail fuel sales business actors who do not have legality and business licenses stipulated by the Government and have the aim of seeking individual profit. This paper aims to determine the regulation of fuel sales and the sociology of law on the legality of retail fuel sales. This research is an empirical juridical research with a descriptive approach conducted in Dinoyo District, Malang City. Based on the results of research on public legal awareness about the legality of retail fuel sales, it is still not said to be legally aware. Due to some of the indicators, people tend to ignore and ignore the legality of the commercial business license on BBM. Keywords: Business Legality; Oil Fuel; Retail Sales of Fuel Oil